Technological Impact on Productivity and Profitability in Mulberry Silk Cocoon Production - Hiriyanna; P. Kumaresan; T.S. Mahadevamurthy; A.S.Suma; S.M.H. Qadri (Journal of Agricultural Extension Management, 2025)
India is the largest consumer of natural silk in the world and the demand for silk is consistently increasing in the country. As a result, the demand-supply gap is widening in mulberry raw silk. Hence, there is an urgent need to improve the production, productivity and quality of Indian silk for meeting the import substitute for domestic market and compete in the international market especially in the changing scenario of global trade